Ecology of the diurnal lizards community in the Reserva Nacional de Paracas, Ica, Peru - Pérez Z, José (2006)
In present paper we study some ecological aspects of the diurnal saurian community of National Reserve of Paracas (RNP) since April to September 1999.”. The spatial distribution, habitat uses (spatial niche), activities patterns (temporal niche) and the diet (trophic niche) of these reptiles were analyzed with the objective of identifying the main differences that will allow a division in the use of the resources. Ctenoblepharis adspersa (bigheaded lizard), Microlophus peruvianus (beach lizard), M. theresiae (dune lizard) and M. thoracius icae (grass lizard) were the species studied. Each lizard showed preference for some particular habitat, to exception of M. peruvianus that was present in all the habitats. The activity was concentrated to the half-day, to exception of C. adspersa. The diets were mainly insects. Differences in trophic, temporal and spatial niche were observed and these would facilitate the coexistence in sympatry of species lizards.